A liquidity crunch in an endogenous growth model with human capital. (14th November 2021) - Salas, Sergio
Abstract: There is by now reasonable evidence that supports the notion of a trend break in the U.S. GDP since the Great Recession. To explain this phenomenon, I construct a version of the Lucas endogenous growth model, amplified with financial frictions and financial disruptions in the firms' sector. I then show how a transitory liquidity crunch is capable, at least qualitatively, of producing a similar pattern of a persistent downward shift in the GDP trend as one could infer happened in the United States since 2008. The main mechanism by which such a result is found relies on workers' decisions on providing labor to firms versus accumulating human capital. I show that a transitory liquidity crunch reduces the demand of labor. Workers anticipating a phase of depressed wages make the decision of accumulating more human capital in the short run, thereby reducing labor supply to firms. In the long run, however, incentivized by a strong recovery, workers decrease human capital accumulation and increase labor supply. Under plausible parameterizations of the model, this situation produces a net effect of a decrease in overall productivity that permanently reduces the trend at which the economy was growing prior to the crisis.